Desain Sistem Perhitungan Emisi Karbon Bahan Bangunan - Suranto, Rahmat; Rudi Waluyo; Subrata Aditama Kittie Aidon Uda (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2023)
Building materials through the production process are materials that produce carbon emissions that can cause global warming and have a very wide impact to affect life on Earth. Regulations on greenhouse gas control towards low-carbon development were created in order to more accurately measure greenhouse gas emissions. The development of information technology that occurs in the current era allows information technology users to complete information technology-related tasks more easily. Manual calculation of carbon emissions takes more time. The more building materials are used, the more calculations are made, so the human error rate is very high. This study aims to design a system of calculation of carbon emissions of building materials. System design is designed using Unified Modeling Language method to describe the interaction of actors with the system consisting of Use Case diagrams, Activity diagrams, Data Flow Diagrams and Entity Relationship diagrams. There are two actors in the design of this system, namely admin and user who perform different functions to the system. The design of carbon emission calculation system of building materials produced is designed using modeling: Use Case Diagram, Activity Diagram, Data Flow Diagram (DFD). the Entity Relationship Diagram (ERD). There are two actors in the design of this system, namely admin and user who perform different functions to the system. Administrator or admin is someone who is responsible for managing, maintaining and operating a system, while the user is the user of a system